2007
DOI: 10.1016/j.neuropsychologia.2006.06.013
|View full text |Cite
|
Sign up to set email alerts
|

False recognition of incidentally learned pictures and words in primary progressive aphasia

Abstract: Recognition memory was tested in patients with primary progressive aphasia (PPA), a language based dementia with relative preservation of memory for at least the first 2 years. The goal of the study was two-fold: (1) to compare true and false recognition rates for words versus pictures in patients with PPA and cognitively intact controls and (2) to determine if the semantic relatedness of distracters-to-targets influences recognition memory performance. Overall, performance of PPA patients was worse for words … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
9
0
3
Order By: Relevance
“…We conducted a previous study in which PPA patients viewed words and pictures in an incidental recognition memory task and gave abnormally high false positive response rates compared with cognitively normal individuals, primarily to semantically related words [18]. The number of target stimuli and distracters in that study was much greater than the 6 stimuli on the 3W3S task and this additional load may have contributed to the emergence of false-positive responses, a phenomenon that was not observed in the current study.…”
Section: Discussionmentioning
confidence: 48%
“…We conducted a previous study in which PPA patients viewed words and pictures in an incidental recognition memory task and gave abnormally high false positive response rates compared with cognitively normal individuals, primarily to semantically related words [18]. The number of target stimuli and distracters in that study was much greater than the 6 stimuli on the 3W3S task and this additional load may have contributed to the emergence of false-positive responses, a phenomenon that was not observed in the current study.…”
Section: Discussionmentioning
confidence: 48%
“…For instance, Rogalski et al [27] have shown that aphasia in PPA patients contributes to the difficulty they experience in choosing items within the same semantic class. One can thus hypothesize that PPA patients may have been unable to distinguish the potential differences between several decks of cards; perhaps, these were all interpreted as part of the same semantic category (i.e., they were unable to process the differences between the "safe" and the "risky" decks on the IGT).…”
Section: Discussionmentioning
confidence: 99%
“…Conforme Rogalski et al (2007), a prevalência da afasia logopênica em indivíduos com histórico de dificuldades de aprendizagem e dislexia do desenvolvimento é o dobro da encontrada na população normal. Neste tipo de afasia, a disfunção da linguagem não se limita as características típicas como dificuldade em encontrar palavras e memória de trabalho, mas se estende ao sistema linguístico, afetando a produção sintática, a codificação fonológica e as representações semânticas (ROGALSKI et al, 2007).…”
Section: Afasia Progressiva Primáriaunclassified
“…Neste tipo de afasia, a disfunção da linguagem não se limita as características típicas como dificuldade em encontrar palavras e memória de trabalho, mas se estende ao sistema linguístico, afetando a produção sintática, a codificação fonológica e as representações semânticas (ROGALSKI et al, 2007).…”
Section: Afasia Progressiva Primáriaunclassified